Predictive Factors of Acute Renal Failure in the Neonates with Respiratory Distress Syndrome - Azar Nickavar; Farhad Abolhasan Choobdar; Ali Mazouri; Atefeh Talebi (Mashhad University of Medical Sciences, 2018)
Background: Preterm birth occurs in a large number of pregnancies, and its incidence has been reported to be on the rise. Acute kidney injury (AKI) is a common complication in the premature infants with respiratory distress syndrome (RDS). The present study aimed to determine the predictive factors, clinical courses, and outcomes of AKI in the neonates with the clinical and radiological manifestations of RDS. Methods: Medical records of 84 premature neonates with RDS were evaluated in two groups of case (with AKI) (n=34) and control (without AKI) (n=50). Diagnosis of AKI was based on the increased level of serum creatinine (>1.5 mg/dL) after the third day of birth or increasing serum creatinine level. In addition, blood pressure and laboratory findings, including complete blood count, serum electrolytes, and urine volume, were compared between the two groups. Results: Mean age of the infants with AKI was 5.41±3.29 days, and the majority of the patients had nonoliguric renal failure. Among the samples, 23.5% died, and 76.5% were discharged without renal impairment. Birth weight, systolic blood pressure, blood urea nitrogen, calcium, and pH on admission had significant correlations with the presence of AKI. Moreover, birth weight was observed to be a relatively accurate predictive factor for AKI (AUC=0.08; 95% CI=0.68-0.91), with 73.5% sensitivity and 80% specificity. Conclusion: According to the results, AKI was more common in the low-birth-weight infants with severe RDS compared to the other subjects